„Iliada” Homera widziana oczyma ilustratorów – Johna Flaxmana i Stanisława Wyspiańskiego - Kossak-Nowocień, Hanna (Studia Europaea Gnesnensia, 2024)
This paper is a contribution to studies into the reception of ancient literary works, focusing on the reception of one of the greatest masterpieces of antique literature, The Iliad. Homer’s epic has repeatedly inspired both other ancient authors and artists of later periods. This was also the case with two exceedingly versatile artists, John Flaxman and Stanisław Wyspiański. Rather than go into analytical comparisons of the scenes they recreated, this study attempts to highlight the professional approach of both artists to their commissions, outline their respective techniques and the manner in which they envisioned the stories they would subsequently depict.